Improved System Frequency Regulation Capability of a Battery Energy Storage System - Huang, Jiejie; Yang, Dejian (Frontiers in Energy Research, 2022)
As a large scale of renewable energy generation including wind energy generation is integrated into a power system, the system frequency stability becomes a challenge. The battery energy storage system (BESS) is a better option for enhancing the system frequency stability. This research suggests an improved frequency regulation scheme of the BESS to suppress the maximum frequency deviation and improve the maximum rate of change of the system frequency and the system frequency of the steady state. To this end, the droop control with the input of the system frequency excursions is employed into the controller of the BESS. To improve the frequency-supporting capability and prevent the over-discharging phenomenon, the control coefficient is defined as a proportional function of the instantaneous state of charge of the BESS and excursions of the system frequency. The contributions of the proposed frequency regulation scheme are investigated with various wind power penetration level conditions and disturbances. Results clearly indicate that the proposed frequency regulation scheme of the BESS is able to achieve objectives in terms of enhancing the maximum frequency excursion, the system frequency of the steady state, and the rate of change of the system frequency under various wind power penetration level conditions, initial SOCs, and disturbances.